Tempo concesso e tempo negato nella relazione medico-paziente: Un’applicazione del sapere antropologico alla pratica del consenso informato - Quagliariello, Chiara (Antropologia Pubblica, 2024)
<header> This article analyses the multiple factors that determine the amount of time consecrated by doctors to inform the patients on the diagnostic and therapeutic procedures that should be performed on their body. The first part of the essay examines the division of time within the hospital, which appears often inadequate to establish a dialogue with patients. In the second part of the essay I highlight how the “lack of time” discourse proposed by doctors only partially corresponds to the amount of time available for the information and the listening of patients. As I substantiate in my contribution, a wide range of factors, not always connected with the material restrictions imposed by the medical patterns of work, contributes in the managing of time dedicated to the information process. The power relations within the medical staff, as the social characteristics of the patients (age, instruction, social identity, geographical origin), influence the information process and, more generally, the “quality” of patient-doctor interactions. In the third part of the article, I focus on how patients are increasingly deploying strategies to gather information about their illnesses and therapies on their own. Such gathering of information takes place primarily within the family group, through the Internet and through the exchanges with other patients in the hospital. My contribution, inspired by a socioanthropological approach, intends to stress the main issues affecting the informed consent system, a realm often studied from a legal perspective only. As I will argue, the deployment of anthropological concepts and methods within medical institutions allows to effectively reveal many of the limits in the doctor-patient interactions and the informed consent system. Finally, my article proposes a meta-disciplinary reflection discussing the ethical conditions of ethnographic research and the possible roles that anthropological knowledge might play within medical institutions. </header>